AN ANALYSIS OF THE STARTUP ECOSYSTEM IN UZBEKISTAN: INSIGHTS FROM U-ENTER AND ERGO ANALYTICS SURVEY - Rijichenko Oleg Radievich (Scholar Express Journals, 2025)
This study presents an in-depth analysis of the startup ecosystem in Uzbekistan, based on a survey of 310 startups conducted by U-Enter in collaboration with ERGO Analytics. The research focuses on the stages of startup development, the challenges faced by entrepreneurs and the sectoral distribution of startups in Uzbekistan. It also examines the relationship between entrepreneurs and investors, particularly the level of trust in investors. The results indicate that a significant number of startups are still in the early stages of development, with funding, customer acquisition and legal support being the primary challenges. The study provides recommendations for policymakers, investors and startup ecosystem players to foster a more conducive environment for entrepreneurship in Uzbekistan
Keywords: startups; innovation; business models